Adjustment speed towards target capital structure and its determinants in Pakistan - Memon, Pervaiz Ahmed (2015)
This study investigates the dynamism of the capital structure of the non-financial listed firms in Pakistan for the period from 2003 to 2012. Specifically, the main objectives of the study are to estimate the adjustment speed towards target capital structure, determining the factors affecting the adjustment speed towards target capital structure, and identifying the factors affecting the target capital structure. Firm specific and country specific factors are used to investigate the determinants of adjustment speed and target capital structure. Difference Generalized Method of Moments (GMM) is used as the estimation technique to avoid the endogeneity and serial correlation problems. The study confirms the existence of optimal capital structure for Pakistani non-financial listed firms, and concludes that firms make full adjustment towards optimal capital structure in 1.46 years to 2.03 years, depending upon the proxy of target debt used. Similarly, factors affecting adjustment speed towards target are also found to be dependent upon the proxy of debt used. Firms’ profitability, stock market development, and distance are found to be relatively consistent determinants of the adjustment speed. Firm and country specific factors affecting target capital structure are also found to vary across the proxies of debt used. However, tangibility, earning volatility, cash, and industry median leverage appear consistently and significantly affecting the target leverage. Interest rate, the only country specific factor, is found to affect target debt when total liabilities to total assets and total debt to total assets are used as measure of the debt. This study contributes in the existing literature of the capital structure by providing evidence regarding the existence of target capital structure in Pakistan. In addition, this is the first attempt that estimates the adjustment speed towards target capital structure, and identifies factors affecting adjustment speed towards target capital structure for Pakistan using four different proxies of leverage.